2017
DOI: 10.47672/ijbs.139
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Innovation on Service Delivery in the Public Sector in Kenya

Abstract: Purpose: The purpose of this study was to assess the effect of innovation on service delivery.Methodology: The study adopted descriptive research design. The study adopted a descriptive analysis by use of descriptive statistics such as mean and frequencies. The target population in this study was 280 employees working in Nairobi GPO. A mixed sampling technique was adopted. The sample size of this study was 65 employees of Nairobi GPO Huduma Centres and 5 members of the public. This study used primary data. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
1
0
1
Order By: Relevance
“…Penelitian-penelitian tersebut terutama tertuju pada upaya untuk meningkatkan penyampaian layanan publik, memperbaiki administrasi publik, dan mengatasi kesenjangan digital dalam masyarakat. Tema public service delivery menyoroti upaya pemerintah untuk memberikan layanan yang lebih efektif dan efisien kepada masyarakat, sementara tema public administration menekankan pentingnya mengelola administrasi publik secara baik dan efektif (Kalu, 2018;Kenenissa & Cho, 2017;Lau et al, 2008;Negumbo, 2018;Nkanata & Ocholla, 2023;Nzimakwe, 2012;Reddick & Turner, 2012;Saxena, 2017;Visser & Twinomurinzi, 2008;Wambugu et al, 2017). Di sisi lain, tema digital divide menunjukkan kekhawatiran akan kesenjangan akses dan pemanfaatan teknologi informasi antara berbagai kelompok dalam masyarakat (Bhuiyan, 2011;Mesa, 2023;.…”
Section: Gambar 1 Overlay Visualization "E-government" Dan "Public Se...unclassified
“…Penelitian-penelitian tersebut terutama tertuju pada upaya untuk meningkatkan penyampaian layanan publik, memperbaiki administrasi publik, dan mengatasi kesenjangan digital dalam masyarakat. Tema public service delivery menyoroti upaya pemerintah untuk memberikan layanan yang lebih efektif dan efisien kepada masyarakat, sementara tema public administration menekankan pentingnya mengelola administrasi publik secara baik dan efektif (Kalu, 2018;Kenenissa & Cho, 2017;Lau et al, 2008;Negumbo, 2018;Nkanata & Ocholla, 2023;Nzimakwe, 2012;Reddick & Turner, 2012;Saxena, 2017;Visser & Twinomurinzi, 2008;Wambugu et al, 2017). Di sisi lain, tema digital divide menunjukkan kekhawatiran akan kesenjangan akses dan pemanfaatan teknologi informasi antara berbagai kelompok dalam masyarakat (Bhuiyan, 2011;Mesa, 2023;.…”
Section: Gambar 1 Overlay Visualization "E-government" Dan "Public Se...unclassified
“…This is also supported by previous research, from Musara and Fatoki (2010) that technological innovation in the banking service sector has resulted in increased efficiency and reduced banking costs for customers of Alice city in South Texas. Wambugu et al (2016) stated that innovation in the public sector in Kenya has a major influence on SD, such as reducing time for SD, and increasing accountability and transparency. Then, it was found that there was a direct and positive relationship between innovation and performance in various service sectors in China (Lin, 2011) and Italy (Ordanini and Parasuraman, 2011), where companies that clearly define their innovation processes for services can be faster and more successful in developing new services.…”
Section: Relationship Between Si and Sdmentioning
confidence: 99%
“…For instance, Rank Xerox was able to reduce its contract refinancing process from a cycle time of 112 days to just a day after reengineering (Malenje, Otanga & Wabwoba, 2014). However, in Kenya, just like many other African countries, public service delivery has not been serving the public interest within it's most optimal capability due to bureaucratic systems and lack of accountability which is characterized by delayed services, long queuing and rampant corruption (Wambugu, Wachira & Mwamba, 2016). In response, various reforms have been undertaken in Kenya to overhaul administrative systems to improve good governance and public service delivery.…”
Section: Statement Of the Problemmentioning
confidence: 99%